An Automated Model Generation Approach for High Level Modelling - Xia, Likun; Bell, Ian; Wilkinson, Antony (2008)
Over the last few years automated model generation has become an increasingly important component of methodologies for verification of large, complex mix-signal SoCs (system-on-chips) and SiPs (system-in-packages). In this paper a novel approach termed Multiple Model Generation System using Delta operator (MMGSD) is developed for extracting either single-input single-output (SISO) or multiple-input single-output (MISO) macromodels from a SPICE netlist. This model generation process detects nonlinearity through variations in output error. Examples of the application of MMGSD are presented for simple two-input systems incorporating a two-stage CMOS operational amplifier (op amp). We demonstrate the generated models are able to model various circuits with good accuracy.